Factors Affecting The Attitude Of Secondary School Teachers Towards Representation Of Women In School Leadership Positions (Journal of Pharmaceutical Negative Results, 2023)
The issue of women in school leadership and administrative positions has been a matter of concern worldwide. This is because it had a negative impact on female capabilities with regard to their leadership and administrative roles in different organizations in general and those of educational institutions in particular.  In many countries, including India, women are regarded as people who cannot lead and manage schools as men can do.  Although women comprise over two-thirds of the teacher population, men dominate the positions of school administration.  There are several studies on the representation of women in school leadership positions. But it remains unexplored in Indian context. The present study is an attempt to explore the factors affecting the attitude of secondary school teachers towards representation of women in School Leadership positions in relation to certain demographic variables, viz., gender, designation, type of school management and location of the institution. Descriptive Survey method has been adopted in this study. The sample consisting of 350 teachers (150 Male and 200 Female) from 40 secondary schools of Visakhapatnam district has been selected using Stratified Random Sampling method. The data were collected using a questionnaire developed and standardized by the researchers.  The tool consists of 30 items (10 items from each of the three attitudinal dimensions) to find out the attitude of secondary school teachers towards representation of women in School Leadership positions. The data were analyzed using different statistical techniques such as means, standard deviations, t-tests and one-way Analysis of Variance (ANOVA). The major findings of the study revealed that the variables – gender and location of the institution have a significant positive influence on the attitude of teachers towards representation of women in School Leadership positions. However, designation and type of school management have no influence on their attitude towards representation of women in School Leadership positions.